Pengungkapan Hak Asasi Manusia Dan Anti Korupsi Pada Perusahaan Manufaktur Dan Perbankan Di Indonesia Tahun 2018-2020 - Zena Zena (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
This research purposes to analyze human rights and anticorruption disclosure at Indonesian manufacturing and banking corporation listed at indonesia stock exchange 2018-2020.Variable used in the research was human rights and anticorruption disclosure. This research is done at manufacturing and banking company listed on Indonesia Stock Exchange 2018-2020 This research used random sampling, it was found that 77 companies consist of 51 manufacturing companies and 26 banking companies as the research sample. Research used statistic descriptive analysis as analysis method. The result of this research showed that has difference for human rights and anticorruption disclosure index on Indonesian manufacturing and banking corporation. The result of this research showed human rights and anticorruption disclosure index at Indonesian manufacturing and banking was low and middle.